ANALYSIS OF LOCAL WHEAT GRAIN PROCESSING TECHNOLOGY - Zufarzhon Zafarovich Kodirov (Journal of new century innovations, 2022)
Development of recipes and technology for the preparation of new varieties of bread and bakery products using durum wheat gluten, improving the rheological properties of dough due to the protein content of wheat gluten, increases the quality, nutritional and biological value of bread and bakery products. Various bread and bakery technologies were developed based on wheat gluten, and the physicochemical and organoleptic characteristics of the finished product, as well as the content of ash and dry matter were studied. Based on the research, samples were taken from the planned products and technological schemes were formed.